The evolutionarily conserved kinase SnRK1 orchestrates resource mobilization during Arabidopsis seedling establishment. Issue 1 (10th November 2021) - Henninger, Markus; Pedrotti, Lorenzo; Krischke, Markus; Draken, Jan; Wildenhain, Theresa; Fekete, Agnes; Rolland, Filip; Müller, Martin J; Fröschel, Christian; Weiste, Christoph; Dröge-Laser, Wolfgang
Abstract: The onset of plant life is characterized by a major phase transition. During early heterotrophic seedling establishment, seed storage reserves fuel metabolic demands, allowing the plant to switch to autotrophic metabolism. Although metabolic pathways leading to storage compound mobilization are well-described, the regulatory circuits remain largely unresolved. Using an inducible knockdown approach of the evolutionarily conserved energy master regulator Snf1-RELATED-PROTEIN-KINASE1 (SnRK1), phenotypic studies reveal its crucial function in Arabidopsis thaliana seedling establishment. Importantly, glucose feeding largely restores growth defects of the kinase mutant, supporting its major impact in resource mobilization. Detailed metabolite studies reveal sucrose as a primary resource early in seedling establishment, in a SnRK1-independent manner. Later, SnRK1 orchestrates catabolism of triacylglycerols and amino acids. Concurrent transcriptomic studies highlight SnRK1 functions in controlling metabolic hubs fuelling gluconeogenesis, as exemplified by cytosolic PYRUVATE ORTHO PHOSPHATE DIKINASE (cyPPDK). Here, SnRK1 establishes its function via phosphorylation of the transcription factor BASIC LEUCINE ZIPPER63 (bZIP63), which directly targets and activates the cyPPDK promoter. Taken together, our results disclose developmental and catabolic functions of SnRK1 in seed storage mobilization and describe a prototypic gene regulatory mechanism. As seedling establishment is important for plant vigor and crop yield, our findings are of agronomical importance. Abstract : Seedling establishment and seed storage compound catabolism are coordinated by the SnRK1 master kinase, as exemplified for SnRK1-mediated transcriptional control of hub genes in gluconeogenesis.